Psicossocial attendance the Aids: the searchfor the subjective questions - Saldanha, Ana A.W.; Figueiredo, Marco A.C.; Coutinho, Maria da Penha L. (Brazilian Journal of Sexually Transmitted Diseases, 2004)
Introduction:having as base the necessity of magnifying of structure of psychological support for carriers of the HIV-Aids, this study if justifies for thecomplexity of the attendance, where the psicossocial counterpart of the illness demands an integrated and extended structure that can complement the boar-ding to multidiscipline currently excused to the patient. Objective:to search subsidies for a reorientation in the boarding to the patient. Method:inside ofthe qualitative boarding of research, the technique of interview opened for the collection of the history of life of ten soropositivas women for the HIV,while using of Public Services of Health was used, focusing its relations in the way of organization of the assistance given in these services. The analysis ofthe contents of the interviews was carried through on the basis of determined Thematic Categories from the subjects excited in the interviews. Result:thefollowing categories had emerged: The Practical one in Health in theSpeech of the Soropositiva Woman; Professional relation of Health-Patient-Health Service; Devolution of the Diagnosis; Multidisciplinary Staff.Conclusion:the study it emphasizes the synthesis necessity enters the two perspectives that must take advantage in the attendance the people with AIDS:the comprehensive vision of the professional on the perspective of the patient and the envolvement of this with the conditions techniques of the attendance.